(untitled) (Journal of NELTA, 2014)
Task-based language teaching (TBLT) has been a dominant approach in the field of ELT for some time now. However, it has complexities regarding its use in a foreign language context. It is said that focusing only on interaction may not be enough in guiding learners to use language correctly, so learners need exposure to grammar rules, and teachers presume that TBLT does not allow it. But, learners’ attention could be directed to the grammar forms during task planning to facilitate noticing of linguistic code. To this end, this small-scale study collects discourse data from an adult EFL learner to evaluate whether guiding learners’ attention to grammar during pre-task planning is of any help. The study concludes that guiding learners’ attention facilitates in producing more accurate and complex discourse than leaving learners on their own during the task planning. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10333 Journal of NELTA, Vol 18 No. 1-2, December 2013; 92-104